The Effectiveness of “PLANS (Personality Fit Business)” Training on Choosing Business Categories - Ginting, Henndy; Fitria Mustari, Farhanah; Fitria, Annisa (Journal of Entrepreneurship, Business and Economics, 2018)
Many entrepreneur students run their businesses which are not congruent with their personality and it will affect the effectiveness of business performance. According to Holland (1985), congruency between personality and occupation can create personal satisfaction, increase productivity and successful career. The research aims to assess the effectiveness of “PLANS (Personality fit Business)” Training to increase congruency between the chosen business category and personality using Holland theory among entrepreneurship student candidates batch 2018 (N = 85). All of them got the "PLANS" Training which was divided into four sessions: (i) Self Exploration, (ii) Business Insights, (iii) Business Fields Exploration, and (iv) Exploration of Business Potential and Planning. The research was conducted quasi-experimental using pre-test and post-test without a control group. The measurements were based on personality SDS (Self Directed Search) Holland test and newly designed business category questionnaire based on the Standard Classification of Business Field in Indonesia 2015. Data were analyzed using Paired t-test with significance level α = 0.05. The result showed a significant difference of congruency between personality and chose business category before and after the training (t = 4.544, p = 0.00 (< 0.05)), (SD) pre-test = 34.71(29.857) and (SD) post-test = 51.71 (32.383). It means “PLANS” Training is effective in increasing congruency between personality and chosen business category among entrepreneurship college student candidates. Therefore, this research suggests the training to be integrated into entrepreneurship and other business school's curriculum like the School of Business and Management ITB as a guideline before starting their study. Research paper Keywords: Training Effectiveness, Holland Theory, Business Category, Entrepreneurship Reference to this paper should be made as follows: Ginting, H., Mustari, F. F. & Fitria, A. (2018). The Effectiveness of “PLANS (Personality Fit Business)” Training on Choosing Business Categories, Journal of Entrepreneurship, Business and Economics , 6 (2), 45–70.